Artistic Visualization Of Senja Dengan Dua Kelelawar Script By Kirdjomulyo Through Herry Dim's Art Creation Method - purnomo, heny; hari pramono, koko; Indar Moslem, Mochamad Danuar (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2024)
The stage serves as a barrier between the artists and the audience, therefore theatrical activities are inextricably linked to it. In order for a theatrical performance to flow smoothly and for the audience to engage with the performers, the stage is a crucial component. Through artistic communication, aesthetic value is created. In the end, this serves as the foundation for artistic endeavours involving the visualization of artistic arrangements on stage. In order for the artistic arrangement in a performance to become more than just a connected component and instead become a whole theatrical production, the director and artistic director must also be able to give meaning to the various elements. Through the visual medium of performing arts, the audience can be given aesthetic gratification through the implementation of a comprehensive creative arrangement. In addition to using Herry Dim's method of art creation, this piece employs a representational theatre style performance approach with accurate and naturalistic environmental descriptions. The artistic arrangement of the script